2000
DOI: 10.1073/pnas.97.1.436
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for nitric oxide activation of p21 ras /extracellular regulated kinase in neuronal ischemic preconditioning

Abstract: The mechanisms underlying neuronal ischemic preconditioning, a phenomenon in which brief episodes of ischemia protect against the lethal effects of subsequent periods of prolonged ischemia, are poorly understood. Ischemia can be modeled in vitro by oxygenglucose deprivation (OGD). We report here that OGD preconditioning induces p21 ras (Ras) activation in an N-methyl-D-aspartate receptor-and NO-dependent, but cGMP-independent, manner. We demonstrate that Ras activity is necessary and sufficient for OGD toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
239
2
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(259 citation statements)
references
References 55 publications
14
239
2
4
Order By: Relevance
“…This hypothesis was supported by studies in vivo in which inhibition of NMDA receptors with MK-801 during IPC resulted in blockade of ischemic tolerance by IPC in gerbils (Kato et al, 1992b) and in vitro (Pringle et al, 1997b). Gonzalez-Zulueta et al (2000) showed that, during OGD preconditioning in neuronal cell cultures, the signaling cascade was initiated by activation of the NMDA receptors, calcium influx, and production of nitric oxide in an RAS-extracellular signal-regulated protein kinase (ERK)-dependent manner, leading to the development of neuronal tolerance to ischemia.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This hypothesis was supported by studies in vivo in which inhibition of NMDA receptors with MK-801 during IPC resulted in blockade of ischemic tolerance by IPC in gerbils (Kato et al, 1992b) and in vitro (Pringle et al, 1997b). Gonzalez-Zulueta et al (2000) showed that, during OGD preconditioning in neuronal cell cultures, the signaling cascade was initiated by activation of the NMDA receptors, calcium influx, and production of nitric oxide in an RAS-extracellular signal-regulated protein kinase (ERK)-dependent manner, leading to the development of neuronal tolerance to ischemia.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, the extracellular and intracellular calcium chelation was also efficacious in blocking the induction of tolerance by NMDA preconditioning. We conjecture that a critical level of calcium is necessary to stimulate calcium-dependent enzymes, including PKC (Huang et al, 1999;Katsura et al, 1999) and nitric oxide synthase (Gonzalez-Zulueta et al, 2000;Nandagopal et al, 2001), that will lead to a signal transduction pathway that could ultimately play a role in neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Ras activates a number of pathways, but the most important seems to be MAPK, which transmits signals downstream to other protein kinases and gene regulatory proteins. Gonzalez-Zulueta and collaborators reported the essential role of NO activation in neuronal ischemic preconditioning [73] , and also found that preconditioning induced Ras activation in an NMDA receptor-and NO-dependent, but cGMP-independent manner. They also demonstrated that Ras activity was necessary and sufficient for ischemic tolerance induction in neurons.…”
Section: Nitric Oxide/reactive Oxygen Species and Neuroprotectionmentioning
confidence: 99%
“…We first investigated whether sublethal oxygen-glucose deprivation (OGD) induced neuronal ischemic tolerance in murine cortical cultures containing both neurons and glia (days in vitro [13][14][15]. To do this, we have tried to determine both the sublethal and lethal exposure periods of OGD for cultured neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study (14) has revealed that the induction of neuronal ischemic tolerance is dependent on new protein synthesis, and the development of tolerance is blocked by cycloheximide. The authors postulated that the NO/p21 Ras /Raf/Erk pathway is critically involved in the PC-induced ischemic tolerance of neurons.…”
Section: Discussionmentioning
confidence: 99%